Economic Prosperity and Cardiovascular Mortality Further Evidence That All Policy Is Health Policy - Weeks, Bill; Weinstein, James (JAMA, 2021)
Numerous factors are known to contribute to cardiovascular disease prevalence and outcomes, including those related to lifestyle, family history and genetics, and clinical care. However, economic factors, such as those involving wealth, prosperity, employment, and power, also might influence health outcomes, including for cardiovascular disease. For instance, the Whitehall study, a longitudinal investigation initiated in Britain in 1967 and designed to examine the epidemiology of and physiological risk factors associated with myocardial ischemia among 18 403 male British civil servants aged 40 to 64 years old,1 found that smoking, elevated cholesterol levels, and high body mass indices were associated with higher cardiovascular mortality rates after just 5 years of follow-up.2 After 7 years of follow-up, researchers also found that lower “employment grade” (eg, working as a messenger, ie, employees who attended to communications at the time by relaying them, as opposed to those who worked as an administrator) was associated with a higher prevalence of risk factors related to cardiovascular mortality, but also, importantly, substantially higher mortality rates after adjusting for those mortality-related risk factors.3